A convenient synthesis of alkyl-2-(2-imino-4-oxothiazolidin-5-ylidene)acetate derivatives involving an electrogenerated base of acetonitrile. (4th March 2017) - Sbei, Najoua; Haouas, Baya; Chebbi, Monia; Smida, Youssef Ben; Arfaoui, Youssef; Boujlel, Khaled; Benkhoud, Mohamed Lamine
ABSTRACT: We report a simple method for the synthesis of alkyl-2-(2-imino-4-oxothiazolidin-5-ylidene) acetate derivatives3 in good yields under mild conditions. The electrogenerated cyanomethyl base (EGB), obtained from electroreduction of acetonitrile-0.1 M TBABF4, assists the reaction between thiourea derivatives1 and dialkyl acetylene dicarboxylate2 . The expected products, 3 /4, and the structure obtained from X-ray diffraction confirm that the main products are the five-membered heterocycles3 . Furthermore, a mechanism, to explain the reaction pathways, is proposed based on the thermodynamic and kinetic data obtained from quantum calculations. GRAPHICAL ABSTRACT: